Adopting a fictitious autobiography: fabrication inflation or deflation?. Issue 6 (2nd July 2020) - Riesthuis, Paul; Otgaar, Henry; Mangiulli, Ivan; de Tauzia, Romane
ABSTRACT: In the present experiment, we examined whether adopting a fictitious biography would make participants believe in this autobiography. Participants were split up into two conditions: forced confabulation condition and control condition. The forced confabulation condition received a snippet with the fake biography and had to adopt it through several methods (i.e., method acting, journaling, and convincing experimenters in an interview) over an extended period of time. The control condition was told that they partook in an experiment about personal childhood memories. Before, during and after lying participants completed four Life Event Inventories (LEI). Results revealed that after coming forward with the truth participants did not increase nor decrease their belief for the lied about events. Additionally, even after a one-year delay, we found no evidence for either effect. Our findings suggest that more extreme forms of fabrication do not make people believe in their lies.